Radiation dose risk variability and its implication in industrial and mining regions, NW Nigeria: DOI: 10.48129/kjs.15207 - Ologe, Oluwatoyin; Aisabokhae, Joseph (Kuwait Journal of Science, 2022)
The awareness of health-related implications of gamma-ray exposure has heightened in recent years, necessitating deeper and insightful studies into radiological hazard evaluation to mitigate associated adverse consequences and enforce protective measures in the environment. A total of 45 sampled locations each were taken for both industrial and mining sites in northwestern Nigeria to determine the concentration of Potassium-40, Thorium-232 and Uranium-238 radionuclides as applied to radiological hazard analysis. The results of the study showed a consistent variation of radiological hazard indices between the industrial site and the mining site. The mean value of the absorbed dose in the industrial site was 90 nGy/h, whereas the mining site recorded a mean value of 210 nGy/h. Other radiological indices such as radium equivalent factor, external risk assessment, internal index and representative gamma index recorded mean values of 187.68, 0.507, 0.547 and 0.768 respectively, whereas the same hazard indices presented higher values of 412.58, 1.114, 1.231 and 1.675 respectively in the mining site. The annual effective dose deduced in the industrial site showed an average value of 0.118 resulting in a dose risk per year of 0.6%, whereas the mining site showed a higher annual effective dose mean value of 0.258 resulting in an estimated dose risk per year of 1.3% of the entire population. The area under study, especially the mining site, presented some radiological hazard indices higher than the recommended global threshold, hence should be classified as a restricted zone to forestall health-related crises which may manifest among local dwellers.